OPTIMIZING SHADING DEVICES THROUGH THE SHADING EFFECT OF SURROUNDING BUILDINGS - Alifiano Rezka Adi; Jatmika Adi Suryabrata; Eugenius Pradipto (DIMENSI (Journal of Architecture and Built Environment), 2019)
This study focuses on measuring the shading effect of surrounding buildings on the thermal performance of office buildings in Jakarta. It is compared with the shading effect of shading devices to optimize its use. This study uses EnergyPlus program to simulate a hypothetical 3x3block. The results showed that the H/W ratio has greater influence on building thermal performance than the surrounding building envelopes. With H/W ratio 2,7, the shading effect of surrounding buildings will be equivalent to 1,2m shading with an effective shadow angle of more than 360. For example, in a 10 floor building, the use of 1,2m shading is not required until the 8th floor based on the shadow angle in H/W ratio 2,7. At a smaller angle, the shading effect of surrounding buildings will be equal to the shading effect of shading devices with a width of less than 1,2m.